Titration of Cu (II) IONS WITH SOLUTIONS of ORGANIC REAGENTS - Kurbanova D.S.; Khakberdiyev Sh.M. (Genius Journals, 2022)
In the development of methods of amperometric titration of different metal ions mixed with one or two solid indicator electrodes allows to know the voltamperometric nature of the ions of the detected metals, the reagent used and its metal complexes and to select the optimal conditions for this titration.
Keywords: Diphenylthiocarbazone; platinum microdisc electrode; neutral molecule; buffer